Prevalence of Sleep Problems Among Chinese Medical Students: A Systematic Review and Meta-Analysis - Sun, Yuanlong; Wang, Huiying; Jin, Tao; Qiu, Fei; Wang, Xiaolong (Frontiers in Psychiatry, 2022)
Background: Sleep is a necessary physiological process, which is closely related to cognitive function, emotion, memory, endocrine balance, and immunity. The prevalence of sleep problems continues to rise in Chinese medical students, which has a potential influence on living and work. Objective: This study aimed to observe the prevalence of sleep problems among medical students in China. Method: The included cross-sectional studies on the prevalence of sleep problems of medical students in China were retrieved from PubMed, Embase, the Cochrane Database of Systematic Reviews, CNKI, and Wanfang database. An 11-item checklist recommended by the Agency for Healthcare Research and Quality was adopted to evaluate the methodological quality of the included studies. Software Stata 12.0, SPSS 26.0, and R were used to analyze the data. Registration: PROSPERO, CRD 42021237303. Result: The prevalence of sleep problems among Chinese medical students was 27.38%. The subgroup analysis showed significant differences in the prevalence of sleep problems among different regions, educational backgrounds, grades, and university types. The region, latitude, and gross domestic product (GDP) were significant heterogeneous sources of sleep problems. The prevalence is positively correlated with latitude and negatively correlated with GDP per capita. Regular screening and appropriate intervention are recommended for these mental health problems.